2018
DOI: 10.1111/jphs.12225
|View full text |Cite
|
Sign up to set email alerts
|

Applying a best-worst scaling methodology to prioritise important attributes of counselling from community pharmacy users’ perspective, Saudi Arabia

Abstract: Objectives This study aimed to identify community pharmacy users’ relevant counselling attributes and to quantify their relative importance. Methods A total of 22 attributes related to counselling in community pharmacy were identified from a literature review, interviews with local pharmacy users and validation among academic experts. To prioritise the attributes, a best–worst scaling (BWS) object case survey was used. Each respondent was asked to complete 17 choice tasks. In each choice task, the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…One study was multi-method design including literature review, phone interviews, and questionnaire. 29 One study explored patient opinions as part of an intervention trial where patients with diabetes received reminder packages, 30 another study reported a novel instrument for evaluating patient satisfaction with pharmacy services within the Arabic context, 42 and one study used a qualitative (phenomenology) approach employing focus groups. 44…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study was multi-method design including literature review, phone interviews, and questionnaire. 29 One study explored patient opinions as part of an intervention trial where patients with diabetes received reminder packages, 30 another study reported a novel instrument for evaluating patient satisfaction with pharmacy services within the Arabic context, 42 and one study used a qualitative (phenomenology) approach employing focus groups. 44…”
Section: Methodsmentioning
confidence: 99%
“…Two studies were conducted in both community pharmacies and public places/shopping centers. 29,38 Other studies recruited participants from a variety of other public places and government offices, as well as from other patient care settings. 39,[42][43][44]47,50,51,58,[60][61][62]…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective patient counseling is a multifactorial task as it is influenced by the patient's expectations of their pharmacy visits and perspectives of the professional role of the pharmacists working in a community setting, pharmacist questioning skills, patient willingness to answer questions, and differences in pharmacists' and patients' perceptions of the diseases and the treatment (10). However, it has been reported that despite the efforts made by MOH and SFDA to ensure that community pharmacists follow the best practice in performing day-to-day tasks, i.e., drug dispensing and counseling, the services provided are still suboptimal (11).…”
Section: Introductionmentioning
confidence: 99%